The Influence of Supply Chain Management and Net Trade Cycle on Financial Performance - Haitham Nobanee; Fadhel Juma Abbas; Mehmood Khan; Jose Varas (International Journal of Supply Chain Management, 2017)
This research aims to enhance liquidity and profitability of companies via examining the relationship between supply chain management, net trade cycle, and financial performance at manufacturing companies in the Kingdom of Bahrain. Moreover, this research undertakes a broad assessment of the literature to expand the three relationships among supply chain management, net trade cycle, and financial performance in one model as well as measure financial performance by return on assets, return on equity, and operational profit margin. The results show the direct significant relationships between the supply chain management components and the financial performance with the exception of the demand management. Indirect relationship between all supply chain management components and financial performance have been found to be more significant than direct relationship and is moderated by the net trade cycle.